Juniper trees and pistachio nuts: Trust and suspicion as modes of scriptural imagination - Briggs, Richard (Theology, 2009)
Trust and suspicion in biblical interpretation might best be understood as modes of imaginative engagement with the biblical text. This paper explores the extent to which a hermeneutic which implicitly either trusts or is suspicious of Scripture is an appropriate framework for texts which themselves have concerns about the merits or limitations of both trust and suspicion. By way of case studies in biblical and other literary texts, it is suggested that one must strive for an appropriate balance of trust and suspicion in the reading of biblical narrative.